Tunable nonreciprocal transmission based on non-Hermitian optical system with magnetic optical materials in a one-dimensional multilayer structure. Issue 15 (13th October 2022) - Yu, Guanxia; Zhang, Xiaomeng; Feng, Lei; Yu, Shen; Wang, Haodong; Yuan, Guangyao
Abstract : In this study, a one-dimensional composite structure composed of a PT-symmetric system and magnetic optical (MO) materials is designed. The nonreciprocal propagation of a one-dimensional multilayer structure is investigated both theoretically and numerically based on the transfer matrix theory. Different from the single nonreciprocal frequency in the parity-time (PT) system, two adjacent band gaps are changed into a pair of nonreciprocal bands under the effect of MO materials and a PT system above the PT exceptional point, and extraordinary transmissions are inspired in some nonreciprocal frequencies. At the same time, the nonreciprocal propagation bands can be tuned based on the different choices of external magnetic field directions. Furthermore, with an increase in the gain/loss factor, the two nonreciprocal band gaps both disappear and form two bands with an extraordinary transmission at certain frequencies. Such peculiar properties in the composite structure may have broad potential applications in communication and integration devices.